Blinking Bird Brains: A Timing Specific Deficit in Auditory Learning in Quail Hatchlings. (1st March 2016) - Harshaw, Christopher; Lickliter, Robert
Abstract : Contingency perception is critical during infancy, providing the basis for the continuous learning (and re‐learning) of the relation between the developing body, self‐produced actions, and the environment. Nevertheless, relatively few studies have systematically examined the spatiotemporal parameters that optimize learning during development. Here, we present a series of experiments exploring a novel timing‐specific deficit in auditory learning in an animal model, the bobwhite quail ( Colinus virginianus ). In this paradigm, chicks vocalize to hear playback of an unfamiliar maternal call and are later tested for their filial preference for that call over a novel maternal call. Rather than a simple, hyperbolic decline in learning with increased delay between chick vocalization and playback, we found a window—450–900 msec after chicks ceased vocalizing—in which chicks appeared to have difficulty learning and forming a preference for the maternal call. This deficit nonetheless occurred only when the spatial location of call playback switched semi‐randomly during training, suggesting an attentional explanation for this deficit. Our findings indicate that optimization of the temporal parameters in operant paradigms with infants can be complex, particularly if tasks requiring the switching of attention between spatial locations. Our findings may thus be instructive for other developmental research with infants employing operant components.